(untitled) (Jurnal Bahasa Lingua Scientia, 2023)
The decline in the English Proficiency Index (EPI) in Indonesia raises concerns about the outdated ELT pedagogy in Indonesia. This study aims to determine a learning approach using digital learning resources with an innovative multi-sensory approach for grade 8 students by utilizing selected stories from Aesop’s Fables which are curated based on the CEFR (Common European Framework of Reference for Languages) level. This study employs a differentiated learning, student-centered approach to learning and uses reading for emotions as a learning tool to facilitate critical and reflective thinking. Based on the work of Lian (2017) and Sudimantara (2021), this study used a multi-sensory load reduction strategy by utilizing nonverbal elements such as rhythm, intonation, movement, emotion, and aesthetics.The research findings show that utilizing digital multi sensory English learning is a practical and diverse method of teaching narrative texts. Innovative learning resources foster students’ enthusiasm for learning and enhance their academic engagement and performance. However, the study revealed that teachers are still hesitant to adopt this new approach and continue to rely on traditional teaching methods, while students are increasingly eager to explore new and innovative ways of learning. This study emphasizes the importance of embracing innovative learning strategies to improve the quality of education in Indonesia and equip students with the skills necessary to succeed in today’s interconnected world.